From lab to field: validity and reliability of inertial measurement unit-derived gait parameters during a standardised run - Webber, E.; Leduc, C.; Emmonds, S.; Eglon, M.; Hanley, B.; Iqbal, Z.; Sheoran, S.; Chaisson, C.; Weaving, D. (Journal of Sports Sciences, 2024)
The aim was to assess concurrent validity and test-retest reliability of spatiotemporal gait parameters from a thoracic-placed inertial measurement unit (IMU) in lab- (Phase One) and field-based (Phase Two) conditions. Spatiotemporal gait parameters were compared (target speeds 3, 5 and 7.5 m/s) between a 100 Hz IMU and an optical measurement system (OptoJump Next, 1000 hz) in 14 trained individuals (Phase One). Additionally, 29 English Premier League football players performed weekly 3 × 60 m runs (5 m/s; observations = 1227; Phase Two). Mixed effects modelling assessed the effect of speed on agreement between systems (Phase One) and test-retest reliability (Phase Two). IMU step time showed strong agreement (<0.3%) regardless of individual or running speed. Direction of mean biases up to 40 ms for contact and flight time depended on the running speed and individual. Step time, length and frequency were most reliable (coefficient of variation = 1.3-1.4%) but confounded by running speed. Step time, length and frequency derived from a thoracic-placed IMU can be used confidently. Contact time could be used if bias is corrected for each individual. To optimise test-retest reliability, a minimum running distance of 40 m is needed to ensure 10 constant-speed steps is gathered.